Somatotype, training and performance in Ironman athletes - Kandel, M.; Baeyens, J. P.; Clarys, P. (European Journal of Sport Science, 2014)
The aim of this study was to describe the physiques of Ironman athletes and the relationship between Ironman's performance, training and somatotype. A total of 165 male and 22 female competitors of the Ironman Switzerland volunteered in this study. Ten anthropometric dimensions were measured, and 12 training and history variables were recorded with a questionnaire. The variables were compared with the race performance. The somatotype was a strong predictor of Ironman performance (R=0.535; R2=0.286; sign. p<0.001) in male athletes. The endomorphy component was the most substantial predictor. Reductions in endomorphy by one standard deviation as well as an increased ectomorphy value by one standard deviation lead to significant and substantial improvement in Ironman performance (28.1 and 29.8 minutes, respectively). An ideal somatotype of 1.7-4.9-2.8 could be established. Age and quantitative training effort were not significant predictors on Ironman performance. In female athletes, no relationship between somatotype, training and performance was found. The somatotype of a male athlete defines for 28.6% variance in Ironman performance. Athletes not having an ideal somatotype of 1.7-4.9-2.8 could improve their performance by altering their somatotype. Lower rates in endomorphy, as well as higher rates in ectomorphy, resulted in a significant better race performance. The impact of somatotype was the most distinguished on the run discipline and had a much greater impact on the total race time than the quantitative training effort. These findings could not be found in female athletes.